2020
DOI: 10.1002/amp2.10038
|View full text |Cite
|
Sign up to set email alerts
|

Continuous flow synthesis of zeolite FAU in an oscillatory baffled reactor

Abstract: In this work, we report, for the first time, the continuous flow synthesis of zeolite NaX successfully accomplished in a pilot-scale (up to 100 L/h) continuous oscillatory baffled reactor (COBR). The continuous synthesis was achieved by combining the seed-assisted method, in-line mixing of reactants at high temperature and COBR. The use of a COBR not only allowed the same residence time as the batch system, but also a controlled temperature profile, thanks to the plug flow behavior and effective heat transfer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The production on the lab and on the mini‐pilot scale are assessed, and the analysis revealed that the obtained yield in the cycloaddition step is the major factor influencing the environmental impact and cost of production. Lutz et al 8 employed an oscillatory baffled reactor for the continuous synthesis of zeolites, which enabled pilot‐scale production with a throughput of up to 100 L/h. The use of the oscillatory baffled reactor also prevented the sedimentation of the crystals, thus enabling stable long‐term continuous operation.…”
mentioning
confidence: 99%
“…The production on the lab and on the mini‐pilot scale are assessed, and the analysis revealed that the obtained yield in the cycloaddition step is the major factor influencing the environmental impact and cost of production. Lutz et al 8 employed an oscillatory baffled reactor for the continuous synthesis of zeolites, which enabled pilot‐scale production with a throughput of up to 100 L/h. The use of the oscillatory baffled reactor also prevented the sedimentation of the crystals, thus enabling stable long‐term continuous operation.…”
mentioning
confidence: 99%